PENGARUH VARIASI PANJANG PEGAS KOPLING TERHADAP PERFORMA DAN KONSUMSI BAHAN BAKAR PADA HONDA TIGER 200 CC - Panji Laksono Adji; Kuntang Winangun; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2021)
Good acceleration and performance are influenced by the degree of flexibility of the clutch springs. The objective that underlies the implementation of this study is to determine the effect of replacing the clutch spring with different length variations. In this study, the data taken is the torque, power and fuel consumption of each type of clutch spring. In this test, two types of clutch springs were used, namely the standard clutch spring and the TDR type coupling spring which were varied in length (38.31mm), (40.93mm) with the addition of 2mm (42.93mm), (40.31mm) rings. also cutting thread 2mm (38.93mm), (36.31mm). Tests were carried out using a dynotest tool with an engine speed of 4000 rpm to 9000 rpm transmission position six. In the TDR clutch spring (42.93mm) there is an increase in torque of 7.42% with a torque yield of 16.20 Nm at 6000 rpm and an increase in power of 6.61% with a power yield of 14.5 HP at 7000 rpm. For fuel consumption TDR coupling spring at ideal rotation (low-medium), an increase of 9.68%. The decrease in fuel consumption only occurred at the top / high speed of 6.32%. For the test results pertalite ethanol fuel, there is a decrease in fuel consumption compared to pertalite fuel for all RPM variables